2020
DOI: 10.1039/c9mh01142k
|View full text |Cite
|
Sign up to set email alerts
|

A centimeter scale self-standing two-dimensional ultra-thin mesoporous platinum nanosheet

Abstract: A kind of mesoporous 2D Pt nanosheets with unique structural features exhibits a high electrocatalytic activity towards the oxygen reduction reaction (ORR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…For example, centimeter‐scale free‐standing mesoporous Pt nanosheets prepared through the Si wafer solid surface oriented assembly of single micelles demonstrated a higher onset potential and a larger diffusion limited current density than commercially available Pt/C materials in an acidic condition, suggesting that the 2D nanosheets patterned with ordered mesopores are beneficial for the ORR activity. [ 39 ] Moreover, the incorporation of Ni metal to make composite mesoporous PtNi nanosheets further increased the performance of Pt, which was resulted from the enhanced absorption for both O and OH intermediates after Ni doping, as suggested by the DFT calculation ( Figure ). To develop much cheaper electrocatalysts, great efforts have been devoted to develop non‐precious transitional metal‐based electrocatalysts.…”
Section: Applicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, centimeter‐scale free‐standing mesoporous Pt nanosheets prepared through the Si wafer solid surface oriented assembly of single micelles demonstrated a higher onset potential and a larger diffusion limited current density than commercially available Pt/C materials in an acidic condition, suggesting that the 2D nanosheets patterned with ordered mesopores are beneficial for the ORR activity. [ 39 ] Moreover, the incorporation of Ni metal to make composite mesoporous PtNi nanosheets further increased the performance of Pt, which was resulted from the enhanced absorption for both O and OH intermediates after Ni doping, as suggested by the DFT calculation ( Figure ). To develop much cheaper electrocatalysts, great efforts have been devoted to develop non‐precious transitional metal‐based electrocatalysts.…”
Section: Applicationsmentioning
confidence: 96%
“…By using a similar concept but a different 2D patterning methodology, a centimeter‐scale freestanding mesoporous Pt nanosheets were prepared through the conformed assembly of core–shell–corona single micelles made of poly (styrene‐ b ‐2‐vinyl pyridine‐ b ‐ethylene oxide) (PS‐ b ‐P2VP‐ b ‐PEO) triblock copolymers on Si wafers (Figure 6f–j). [ 39 ] In a typical synthesis, the pure PS‐ b ‐P2VP‐ b ‐PEO block copolymer micelle methanol solution was first prepared through a dialysis method. Then, the adjustment of the solution pH to acidic triggered the protonation of P2VP, which can further interact with the negatively charged PtCl 6 2− ions by electrostatic attraction to form PS‐ b ‐P2VP‐ b ‐PEO/PtCl 6 2− composite micelles.…”
Section: Bottom‐up Assembly Of Single Micelles Toward 2dommsmentioning
confidence: 99%
“…[54] Synthesis of centimeter scale mesoporous film with single-layer template by single-layer micelle film laid on the substrate has also been realized. [55] Specific steps are spin-coating the methanol solution of PS-b-PVP-b-PEO and H 2 PtCl 6 on the SiO x /Si substrate, and evaporating solvent (Figure 5f). Under the atomic force microscope (AFM), it can be observed that the single-layer PS-b-PVP-b-PEO spherical micelles are arranged in an orderly manner on the substrate when the micelle concentration is adequate (Figure 5k-n).…”
Section: Soft Template Strategymentioning
confidence: 99%
“…The PS-P2VP-PEO micelle concentrations are k) 0.1, l) 0.2, m) 0.4, and n) 0.8 mg mL −1 . Reproduced with permission [55]. Copyright 2020, The Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…[ 18 ] Large‐sized structure like bulk structure possesses high stability in structure, but limited exposed surface and massive sites not utilized inside are obstacles for applications. [ 19,20 ] Porous nanostructures with higher surface‐to‐volume ratios exhibit higher activity by providing more active sites for contact with reactants, but the reported porous noble metals are generally small in size. Smaller nanostructures are more prone to change in shape or aggregate in performance testing or practical application, leading to a rapid decline in activity over time.…”
Section: Introductionmentioning
confidence: 99%